2015
DOI: 10.1111/nyas.12720
|View full text |Cite
|
Sign up to set email alerts
|

Linking ambient particulate matter pollution effects with oxidative biology and immune responses

Abstract: Exposure to combustion-related particulate matter (PM), at concentrations experienced by populations throughout the world, contributes to pulmonary and cardiac disease through multiple mechanistic pathways that are complex and interdependent. Current evidence supports an interactive chain of events linking pollution-induced pulmonary and systemic oxidative stress, inflammatory events, and translocation of particle constituents with an associated risk of vascular dysfunction, atherosclerosis, altered cardiac au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 51 publications
1
65
0
Order By: Relevance
“…VM is a clinical indicator of disrupted white matter development [80,81] and can be accompanied by significant cognitive deficits [113]. Based on its well-known inflammatory properties [137], UFP exposures would be expected to activate brain microglia, resulting in the release of proinflammatory cytokines [138-140] that could lead to hypomyelination via toxicity to oligodendrocytes, the myelinating cells of the brain [141]. Indeed, particular vulnerability of premyelinating olidgodendrocytes to such consequences of microglial activation has been described [142,143].…”
Section: Discussionmentioning
confidence: 99%
“…VM is a clinical indicator of disrupted white matter development [80,81] and can be accompanied by significant cognitive deficits [113]. Based on its well-known inflammatory properties [137], UFP exposures would be expected to activate brain microglia, resulting in the release of proinflammatory cytokines [138-140] that could lead to hypomyelination via toxicity to oligodendrocytes, the myelinating cells of the brain [141]. Indeed, particular vulnerability of premyelinating olidgodendrocytes to such consequences of microglial activation has been described [142,143].…”
Section: Discussionmentioning
confidence: 99%
“…DE inhalation attenuates vasodilation in response to both endothelium-dependent and nitric oxide donor drugs, but not in response to vasodilators acting via smooth muscle cell receptors; a profile that is suggestive of NO scavenging by O 2 − free radicals (143,206). Exposure to C-DEAP is known to cause a compensatory increase and to eventually deplete antioxidant concentrations in respiratory tract lining fluids and pulmonary cells (207). Likewise, inhalation of DE alters the expression of several antioxidant pathways in peripheral blood monocytes (208).…”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%
“…The lung lining fluids surrounding pulmonary epithelial cells in vivo provide an early defense against acute exposure to inhaled pollutants. However, prolonged or repeated exposure leads to depletion of antioxidants in cell surfactants and changes in pulmonary cell function (207). The gases within C-DEAP can modify blood constituents in the pulmonary circulation, although the precise mechanism by which the oxidative “signal” is carried or transferred to peripheral organs requires further investigation (159).…”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%
“…In this study we showed that CA affects epithelial monolayer integrity and paracellular permeability [37]. In addition, the alveolar epithelium participates in immune responses to UPM [38]. So, we focused on disruption of the alveolar epithelial barrier function caused by proinflammatory cytokines and intracellular ROS induced by UPM.…”
Section: Discussionmentioning
confidence: 99%